Parental leave and the glass ceiling in Sweden - James W. Albrecht; Peter Skogmann Thoursie; Susan B. Vroman (Institute for Evaluation of Labour Market and Education Policy (IFAU), 2015)
In this paper, we update and extend "Is There a Glass Ceiling in Sweden?" (Albrecht et al. 2003) by documenting the extent to which the gender log wage gap across the distribution in Sweden has changed over the period 1998-2008. We then examine the Swedish glass ceiling in 2008 in more detail by documenting how it differs for white-collar versus blue-collar workers and for private- versus public-sector workers. We also examine when in the life cycle the glass ceiling effect arises and how this effect develops around the birth of the first child. Finally, we investigate the possible connection between the glass ceiling and the parental leave system in Sweden by linking wage data with data on parental leave from different Swedish registers.
Keywords: J16; J31; J71; 330; gender gap; parental leave; quantile regression